(untitled) (MAUSAM, 1968)
The monthly, wave characteristics of the Arabian Sea are-reported based on an analysis of the wave data published in the Indian Daily Weather Reports of the India Meteorological Department for the period 1960-1964, ,June and July are the roughest months in the Arabian Sea and October the calmest, The maximum height of the highest ten per cent wave which has actually occurred in the month of June is 12.6 m. The direction of approach of such waves ranges between W and SW.